PACKAGING TECHNOLOGY TO SATE TUNA AT KONDANG MERAK, MALANG - ade yamindago; Oktiyas Muzaky Luthfi (Journal of Innovation and Applied Technology, 2016)
Sate tuna is the main menu Kondang Merak Beach area. The product is only sold in limited area, Merak Kondang, due to constrained by geography and food safety (hygiene). The aim of this activity was to improve the quality of sate tuna with processing hygiene and good packaging technology. It is an effort being made to improve the distribution of product marketing tuna satay. Community as producer of sate tuna has been given the knowledge fish handling, choosing tuna meat, sate processing and vacuum packaging technology. From these activity was resulted product of red and white sate, pepes tuna (grilled tuna meat) with good and hygienic packaging. We also gave motivation and business development skill to the community in Kondang Merak.